Physico-chemical Properties and Fish Composition of Ihawan Spring Community Watershed, Tandag, Surigao del Sur, Philippines - Melche D Ojao; Ecclesiastes E Manatadi; Pepito A Logronio; Julianne T Raz; Maricris Gansubin Cudal; Arturo G Gracia Jr. (Journal of Tropical Life Science, 2021)
The first assessment study in aquatic ecosystem of Ihawan Spring Community Watershed revealed 23 species of fish belonging to 21 families from 22 genera. Species diversity is high, with values 1.88 and 0.42, respectively for Shannon-Weiner Diversity Index (Ã¢â‚¬ËœH) and Simpsons Dominance (D). Out of the 21 families, Butidae and Eleotridae had the highest species composition (8.70%). Interestingly, the fish composition of Ihawan Spring Community Watershed was primarily composed of native (19 spp.), one (1 spp.) endemic, with two (2 spp.) recorded introduced species and one (1 spp.) Invasive Alien Species. The presence of dominant species of native species indicates the healthy state of the freshwater ecosystem of Ihawan Spring Community Watershed. However, the recently classified Invasive Alien Species of Oreochromis niloticus or Nile tilapia may attribute a negative impact in the river ecosystem that may result in the possible decline of native and endemic fish species present in the area. Whereas, the in- situ reading of some physico-chemical parameters like temperature, dissolved oxygen (DO) and pH of the Ihawan Spring Community Watershed river ecosystem revealed that all parameter tested have passed the standards set by the Philippine Water Quality Standards for Class AA (potable water) intended primarily for waters having watersheds which are inhabited and otherwise protected. From the findings, additional study especially on the abundance of recorded introduced and Invasive Alien Species is highly recommended to monitor the population abundance between the introduced, Invasive Alien Species, native and endemic species and to establish a real profile of the aquatic ecosystem of Ihawan Spring Community Watershed.